Literasi Keuangan pada UMKM (Studi Pemetaan Sistematis dan Analisis Co-Authorship pada Basis Data Scopus) - Yogi Sugiarto Maulana; Erna Maulina; Nenden Kostini; Tetty Herawati (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2021)
Financial literacy has been widely discussed in various countries with a wide range of subject areas, focuses, and loci. The purpose of this paper is to map the trends of scientific publications and map the network of authors on financial literacy, especially in the MSME sector. We have developed bibliometric analysis through VOSviewer software, supplemented by literature reviews. A total of 126 articles were obtained from Scopus related to the topics "financial literacy" and "micro small medium enterprise". We present trends in financial literacy research, author productivity, and journals, as well as detailing the network of co-authorships who have researched and published in the scientific domain. The results of the study are known that 1) The application of financial literacy in MSMEs only appeared in 2010 and experienced a significant upward trend. 2) Penulis most productive comes from china, where there are 2 authors each produce 3 articles. 3) Co-authorship has not been established between writers in each country and between countries. 4) Indonesia contributes financial literacy publications in MSMEs the most compared to other countries, with the number of publications as many as 34 articles. Lastly, the mapping provides an overview of which countries and writers are concentric and collaborate with each other on the topic of financial literacy in MSMEs.